Microstructure and stress rupture property of titanium-containing 11Cr ferritic/martensitic steels - Yin, Feng-shi; Jung, Woo-sang (Elsevier BV, 2009)
The microstructure and stress rupture behavior of 11Cr ferritic/martensitic steels with 0.02wt.%Ti (low Ti) and 0.14wt.%Ti (high Ti) have been studied. The steels are prepared by vacuum induction melting followed by hot forging and rolling into plates. The results show that titanium is easy to combine with oxygen and other elements to form complex inclusions. Large MX particles with 1-3 mu m are found in the high titanium steel. Most of the large MX particles have a TiO2 cored structure. After normalizing at 1100 degrees C for 1 h, cooled in air and tempering at 750 degrees C for 1 h, nano-sized MX precipitates distribute densely near martenstic lath boundaries in the high titanium steel. The large MX particles cannot be dissolved even at austenitizing temperature up to 1300 degrees C. Creep cracks nucleate at the interface between matrixes and the large MX particles or titanium-containing oxide inclusions. (C) 2008 Elsevier B.V. All rights reserved.